O menino de engenho e o engenho da vida: produção e recepção da literatura zeliniana (1932-1943) - Nascimento, Luís Felipe Gonçalves do (2020)
This work is based on the perspective of an intellectual History. It permeates José Lins do Rego’s trajectory and searches to count the evolution of his projection through intellectual surroundings of the Brazil between 30’s and 40’s decades on twenty century. Besides that, it goes throughout since the regionalist Northeast debates, whose exponent was Gilberto Freyre on the capital of Pernambuco State, until the meeting of the Alagoas State group, in which it discussed an new stage of Brazilian regionalism. Meanwhile, these previous debates composed a genesis of the “Zeliniana” writing, so that, it verified the site of the amplification of his writing was Rio de Janeiro, the central space of the Brazil in that period. Also, it examined the reception of the Rego’s literature by critics, the distinctive eulogies and framings of the publishing club that time, profitable and harmful to the author. As a consequence of they had done that, the work was available to a major numbers of people. It discussed on how the research object, the called Cycle of the Cana-de-açúcar, with emphasis on “Menino de Engenho” (1932) and “Fogo Morto” (1943), years of clipping of the story told in this work. These two works offer a representation of the politics and modernization appeared on the debates started with a oligarchic crisis of 30’s Revolution.